Safety of Direct Trocar Entry in Laparoscopy in a Structured Fellowship Programme - Trehan, Nikita; Padiyath, Hafeez Rehman; Kaur, Amanjot; Dhingra, Mansi; Shriya, Rashmi; Ahmad, Ayesha (International Journal of Human and Health Sciences (IJHHS), 2019)
Introduction:The best method of primary trocar insertion in laparoscopy remains controversial. There are advocates for both initial Veress needle insertion as well as direct trocar insertion. Aim of the study: This study was carried out to find out the complication rate of direct trocar insertion as a method of laparoscopic entry and find out the learning curve of trainees in a structured fellowship programme. Methodology: Retrospective analysis was done over period of 5 years with a sample size of 2053 subjects. Results: 2053 laparoscopic surgeries were examined. Overall complication rate was 0.38%; subjects with previous abdominal surgery were found to have higher complication rate as compared to ones with no history of prior surgery. [0.46% and 0.35% respectively]. All trainees gained reasonable degree of confidence within 6 months. Conclusion: Direct trocar insertion is a safe method of laparoscopic entry, which can be taught to trainees with no prior laparoscopic experience, without an increase in entry complications. International Journal of Human and Health Sciences Vol. 04 No. 01 January’20 Page : 51-54